"I Am More Than What I Look Alike": Asian American Women in Public School Administration. (February 2017) - Liang, Jia "Grace"; Peters-Hawkins, April L.
Purpose: Little research exists that examines the leadership experiences of Asian American women in public schools. This study sought to understand the meanings Asian American women school administrators have constructed out of their professional lives given the intersection of gender, race-ethnicity, and leadership.Research Method/Approach: Data collection primarily relied on semistructured in-depth interviews and informal observations with 11 building-level administrators in two demographically contrasting states in the United States. Data were analyzed through constant comparative methods, using three iterations of initial codes/surface content analysis, pattern variables development, and application to data set.Findings: The Asian American women's paths to leadership were to a large degree emergent and personal. The women embraced a lifetime mission as to make a difference on their students' lives and uplift the social groups embodied in their identities. They struggled with gender, racial-ethnic, and cultural discrimination. Critiques and resistance to racism were often tempered, particularly in their professional lives, as evident in their careful usage of agentic behavior and balanced communal practices. Their agency to fully assume leadership and fight against the oppressive system was a cooperant process of survival, the "I have to, " and resistance, the "I want to and can."Conclusion: By centering on the lived experiences of Asian American women, this study adds a new intersectionality, positionality, and voice to the established knowledge about women of color and educational leadership.